Guideline for the prevention of acute chemotherapy‐induced nausea and vomiting in pediatric cancer patients: A focused update. Issue 10 (28th April 2017) - Patel, Priya; Robinson, Paula D.; Thackray, Jennifer; Flank, Jacqueline; Holdsworth, Mark T.; Gibson, Paul; Orsey, Andrea; Portwine, Carol; Freedman, Jason; Madden, Jennifer R.; Phillips, Robert; Sung, Lillian; et al.
Abstract: This update of the 2013 clinical practice guideline provides clinicians with guidance regarding the use of aprepitant and palonosetron for the prevention of acute chemotherapy‐induced nausea and vomiting (CINV) in children. The recommendations were based on three systematic reviews. Substantive changes were made to the guideline recommendations including the inclusion of palonosetron to the 5‐HT3 antagonists recommended for children receiving highly emetogenic chemotherapy (HEC) and the recommendation of aprepitant for children 6 months of age or older receiving HEC. To optimize CINV control in children, future work must focus on closing critical research gaps.